Evaluation of Anti-anemic Effect of Anthocyanin Rich Oryza sativa L. indica (Black Rice) Seeds Extract (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Oryza sativa L. indica (black rice) has a rich cultural history and used as a tribute food. As the outer layer of seeds contains anthocyanin, O. sativa L. indica is black. Traditionally the plant used to enhance heart health, reduces the risk of atherosclerosis, diabetes as well as allergy, control hypertension, and improves the digestive system and lipid profile. It has anti-inflammatory action, detoxifies the body, decreases cancer growth, supports in weight management, and improve memory and quality of life. Here, the methanolic extract of black rice (BRME) was evaluated for its anti-anemic effect. In study anemia was induced by administering 40 mg/kg phenylhydrazine (PHZ) for two consecutive days in rats. From day 3, animals were treated with standard drug and BRME extracts (200 and 400 mg/kg) till 15 days. The anti-anemic activity was examined by estimating different parameters like hemoglobin, red blood cell, hematocrit, reticulocytes, aspartate amino transaminase activity, alanine amino transaminase and alkaline phosphatase. The results of the phytochemical test revealed the presence of carbohydrates, alkaloids, glycosides, saponins, flavonoids, tannins, amino acid, and triterpenoids. Methanolic extract of black rice also restored the hematological parameter and biochemical parameters values near to normal levels after 13 days of treatment at 200 and 400 mg/kg. The 400 mg/kg dose shows higher anti-anemic effect compared to the lower 200 mg/kg dose. From the result, it is concluded that O. sativa L. indica is a valuable source of active compounds with anti-anemic properties and can be used to treat anemia.